Tracked Changes. Metallic cables and other passive components test methods. Electromagnetic compatibility (EMC). Test method for measuring of transfer impedance ZT and screening attenuation aS or coupling attenuation aC of connectors and assemblies. Triaxial tube in tube method Part 4-7, (7th October 2021) - British Standards Institution
No abstract available